The contribution of Buddhist wisdom to management development. Issue 8 (8th September 2014) - van den Muyzenberg, Laurens
Abstract : Purpose: – The purpose of this paper is to present selected Buddhist concepts that are useful to leaders of business and to those that want to increase the performance of their businesses and of their organisations implementing practical wisdom from a Buddhist perspective. Design/methodology/approach: – The design is to present relevant Buddhist concepts and their application. The methodology used is to consider their logic and rationality, the experiences of Buddhist business leaders in Taiwan and Thailand, and my experience of explaining and applying the concepts. The approach is to present the concepts such a way that the reader can determine if these concept merit further study and trying them out. Findings: – Finding Buddhist wisdom concepts that can be applied to management development often require reformulation from the original texts. The original information is vast and requires selection to those concepts that can be readily understood by non-Buddhists. Research limitations/implications: – At a high level of abstraction core Buddhist concepts are the same but not in detail. In the paper two types of Buddhism have beeb referred to, Theravada and Tibetan traditions, and not for example Zen. Practical implications: – Special emphasis is placed on how to see to it that the values a company describes in its mission, values and business principles statements are practiced. There is always a gap between intentions and results. Where is the gap, how big is it, what can be done about it? Social implications: – Buddhism like all spiritual traditions aims to increase the well-being of all. Buddhist concepts can contribute to reduce conflicts and increase happiness by influencing healthy motivations and intentions, and strengthening self-discipline. Originality/value: – The Buddhist wisdom concepts have been selected together with the scholarly monk Tenzin Gyatso, the 14th Dalai Lama, with profound knowledge of Tibetan Buddhism and with the scholarly monk and abbot of the Nyanavesakavan temple, P.A. Payutto, one of the most brilliant Buddhist scholars in the Thai Buddhist history.